2018
DOI: 10.1371/journal.pone.0191655
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cohort study of the impacts of mild traumatic brain injury in adults four years post-injury

Abstract: There is increasing evidence that some people can experience persistent symptoms for up to a year following mild TBI. However, few longitudinal studies of mild TBI exist and the longer-term impact remains unclear. The purpose of this study is to determine if there are long-term effects of mild traumatic brain injury (TBI) four-years later. Adults (aged ≥16 years) identified as part of a TBI incidence study who experienced a mild-TBI four-years ago (N = 232) were compared to age-sex matched controls (N = 232). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 37 publications
6
82
0
1
Order By: Relevance
“…Therefore, the question remains whether it is necessary to measure both patient-and parent-reported fatigue as was suggested in other studies. 15,51,52 Participation Patients and their parents in this study reported participation restrictions in all domains of participation (median total score 82.5 (IQR 68.8, 92.3), 91.1 (80.0, 96.9), respectively), supporting earlier studies in this patient population (pediatric ABI 27,53 ; adult mTBI 54 ; stroke. 55 ) In the current study, AYAs reported significantly more participation restrictions than their parents, in home, community and school activities.…”
Section: Fatiguesupporting
confidence: 87%
“…Therefore, the question remains whether it is necessary to measure both patient-and parent-reported fatigue as was suggested in other studies. 15,51,52 Participation Patients and their parents in this study reported participation restrictions in all domains of participation (median total score 82.5 (IQR 68.8, 92.3), 91.1 (80.0, 96.9), respectively), supporting earlier studies in this patient population (pediatric ABI 27,53 ; adult mTBI 54 ; stroke. 55 ) In the current study, AYAs reported significantly more participation restrictions than their parents, in home, community and school activities.…”
Section: Fatiguesupporting
confidence: 87%
“…Seven items (subjective sleep quality, sleep latency (the time from lying down for sleep to the start of actual sleep), sleep duration, habitual sleep efficiency (the proportion of actual sleep time spent in bed), sleep disturbances, use of sleep medication and day time dysfunction) are scored on 4 point Likert scales (0e3, low to high), with a total score ranging from 0 to 21 with higher scores representing poorer sleep quality. The PSQI has been used in pediatric 42 and adult TBI studies. 43 2.8.…”
Section: Sleep Qualitymentioning
confidence: 99%
“…Although the emergency department is the typical point of entry into the health care system, increasingly, patients with mTBI are first seeking medical attention from a community-based primary care provider. [11][12][13][14] Primary care providers and specialists (eg, neurologists, physiatrists, etc) unattached to a TBI-specific clinic are often relied on to provide and/or arrange early follow-up care. 15 Traditionally, mTBI has been thought to require minimal clinical management beyond watchful waiting.…”
mentioning
confidence: 99%